Effect of Cadmium Compound on the Histological Changes of Various Vital Organs of the Fresh Water Fish Cirrhinus mrigala - Prabhahar, C (International Journal of Pharmaceutical & Biological Archive, 2012)
ABSTRACTIn the present investigation, the effect of cadmium sulphate on the histology of gill, liver and kidney were investigated in the edible freshwater fish Cirrhinus mrigala. Further its effects an glycogen and protein contents in the gills, liver and kidney were analysed. Histopathological studies on gills, liver and kidney were carried out. The primary and secondary gill lamellae were affected, Pillar cells, epithelial cells and cartilagenous cells were fully damaged; adjacent gill lamellae were fused; necrosis and bulging of tip gill lamellae observed. Ruptured hepatocytes with loss of its polygonal shape, dialated and coagulated blood cells, large vacuoles in the hepatocytes with displaced nucleus observed in the liver of treated fishes. The kidney tissue of cadmium treated fishes showed ruptured tubular cells, vacuoles between the cells, malanomacrophages and brown coloured pigment.